The application of cardiac and renal imaging in the assessment of acute kidney injury and chronic kidney disease - Mahmoud, Huda S. (2022)
Despite pathological diversity, chronic kidney disease and acute kidney injury are inextricably linked in a perpetual cycle of renal and cardiovascular damage and decline.